Measuring CH4 Fluxes From Lake and Reservoir Sediments: Methodologies and Needs - D’Ambrosio, Sofia L.; Harrison, John A. (Frontiers in Environmental Science, 2022)
Accurately quantifying the diffusive flux of CH4 between sediments and the overlying water column is crucial when constructing CH4 budgets in lakes and reservoirs. Although a variety of ex situ and in situ techniques exist for determining this flux, no reviews have provided a comprehensive, comparative overview of these approaches or discussed implications of measurement method on flux estimation. Here, we critically review methods applied in 163 peer-reviewed studies to estimate diffusive CH4 fluxes from lake sediments, including sediment incubations, benthic chambers, and modeling approaches applied in the sediment or water column. For each method, we summarize the approach, discuss limitations and advantages, and summarize published comparisons between different methods. In addition, we examine how method limitations have likely shaped knowledge gaps in current understanding of lake CH4 dynamics. Finally, we call for the development and application of new methods, along with additional testing and intercomparison of existing methods, in order to advance understanding of lake CH4 fluxes.